1104 De-novo sleep apnea in a transgender man on gender-affirming hormone therapy. (27th April 2018) - Lerner, Brian S; Robertson, Brian; Williams, Scott
Abstract: Introduction: Transgender individuals undergoing gender affirming hormone therapy are a unique population for evaluating the effect of sex hormones on obstructive sleep apnea (OSA). Evidence is inconsistent in how testosterone affects sleep disordered breathing at doses typical for androgen replacement in males with low testosterone is inconsistent. Testosterone influences sleep and respiratory stability regardless of sex, and the impact of higher doses, as in gender transition, has not been systematically studied. We present a case of de-novo development of OSA in a transgender man undergoing treatment with testosterone. Report of Case: A 17yo transgender man presented for snoring and daytime sleepiness (ESS 13). Medical history included hypothyroidism, PCOS, obesity, anxiety, depression, and ADHD. He was on fluoxetine, methylphenidate, levothyroxine, OCPs, and aripiprazole, but was not on testosterone at the time of initial evaluation. The pretreatment polysomnogram was unremarkable (AHI=2/hr). Six months after initiating testosterone therapy, his sleep symptoms worsened, and a repeat PSG demonstrated moderate OSA (AHI=25/hr). The BMI had not changed with hormone treatment (33 kg/m2). After 30 days of CPAP (8 cm H2O), the patient demonstrated 100% compliance with an average usage of 10 hours and 55minutes and a residual AHI of 3.9/hr. Self-reported sleep quality improved (ESS 8). Conclusion: To our knowledge this is the first case of the development of sleep apnea in a natal female being treated with testosterone. Further research is needed to evaluate the impact of sex hormone replacement on sleep disordered breathing at doses used for gender transition.